(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this study, researchers compare and contrast issues regarding diabetes self-management between persons in good versus poor glycemic control. The sample comprises low-income racially diverse adults with diabetes from four mid-western community health centers 44 patients participated in eight focus groups divided by control status (HbA1c of > 9 [uncontrolled] or < 7 [controlled]). Themes common to both groups included the impact of dietary restrictions on social interactions, food cravings, the impact of mental health on self-management, and the importance of formal and informal (friends and family) support. Those in the uncontrolled groups described fear about being able to control their diabetes, confusion about self-management, and difficulty managing their diabetes while caring for family members. Although those in the controlled groups acknowledged difficulties, they discussed resisting cravings, making improvements with small changes, positive feelings about their ability to control their diabetes, and enjoying new foods and exercise. Interventions should include mental health support, incorporate formal and informal patient support structures, and address literacy issues. Health care providers and intervention personnel should be very concrete about how to do self-management tasks and guide patients on how to alter their diabetes regimens for social and other important life events.